Group Education Model Improving The Knowledge of School Age Children in Protecting of Sexual Violence - Labir, I Ketut; Sulisnadewi, Ni Luh Kompyang; Ribek, I Nyoman (LPPM Undiksha, 2019)
Cases of sexual violence and abuse in Indonesia are increasingly common. Not only in adults, children are now victims. Some cases of victims or perpetrators involve underage children. Many parents feel taboo to talk about early childhood education with children. This causes children not to get information that is supposed to protect themselves from sexual violence. Need to do various efforts to provide education to children about knowledge to protect themselves from sexual violence. The purpose of this study was to determine the effect of sexual violence education on children on efforts to protect from sexual violence. This study uses pre-experimental design with approach pretest-posttest design. The number of samples is 195 children taken by purposive sampling technique. Analyze data using different Wilcoxon Signed Rank test with 95% significance level, p ≤ (0.05). The results showed that the average age of the respondents was 10.2 years and most of the men were 52.8%. Before giving education, the average score of respondents' knowledge about efforts to protect themselves from sexual violence was 6.7 and increased to 7.79 after giving education. There is a difference in knowledge about efforts to protect themselves from sexual violence before and after being given education (p value ≤ 0.001; <α = 0.05). It is recommended that the provision of information about sexual violence be given regularly by teachers and parents.Keywords: Education - Elementary School Age Knowledge - Efforts to Protect Themselves from Sexual Violence